Sistema tributário, governança corporativa e abertura de capital: Brasil versus Estados Unidos - Almeida Júnior, Elemar Sebastião da (2007)
With the objective of improving their market image and, consequently, the demand for its shares, companies use Corporate Governance practices as a way to increase the consistency of the financial statements and as a guarantee of respect to the minorities shareholders rights. In the last three years, the increase in the number of corporations that performed an IPO in Brazil, has boosted the search to implement Corporate Governance practices in not open capital companies who intend to open their capital. The standard Corporate Governance structure to perform an IPO operation in the new segments of the São Paulo Stock Exchange (BOVESPA) assumes the adoption of practices that, among other characteristics, increase the company disclosure and the strictness in dealing with account and tax issues that can affect their results. Those effects are taken in consideration during the process of the IPO go - no go -decision. In this sense, the objective of the research was to analyze, comparatively to the North-American case, if the structure of the Brazilian tax system has characteristics that motivates or not the IPO decision in the new corporate governance situation. Beyond those features that can have direct effects to the management of results by the companies, the research studied tax and legal aspects that could have indirect influence in the IPO decision, as it stimulates the investment in the stock market and the growing of the capital market. The main motivation for this research was to make clear the challenges that the adoption of the standard corporate governance structure can bring to the companies, in terms of the treatment of its fiscal and tax issues, and its impacts in the IPO decision.